PENGARUH KEPERCAYAAN MEREK TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK HANDPHONE VIVO DI KALANGAN MAHASISWA S1 UNIVERSITAS TADULAKO - Puteri, Anindya (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The purpose of this study is to know and analyze the influence of brand trust on purchasing decisions. The variables of this research are brand characteristics (X1), company characteristics (X2) and brand consumer characteristics (X3). While the dependent variable is Purchase Decision (Y). The research method used is descriptive method causal with the number of samples 88 people with purposive sampling techniques and methods of analysis, Multiple Linear Regression with the help of computer programs SPSS for windows, Release 25.0. The result of research shows that there is influence of brand trust consist of characteristic of brand, characteristic of company and characteristic of consumer brand to consumer decision to buy vivo handphone product among student of tadulako University S1 simultantly or partially